Kilovoltage intrafraction monitoring for real-time image guided adaptive radiotherapy reduces total dose for lung SABR. Issue 1 (October 2016) - Juneja, Prabhjot; Caillet, Vincent; Shaw, Tom; Martland, Judith; Booth, Jeremy T.
Abstract: This study presents estimation of typical kV fluoroscopic imaging doses for image-guided real-time adaptive radiotherapy. For a cohort of 10 lung SABR patients the estimated imaging dose to ipsi-lateral lung with real-time adaptation is 9.9–15.1 cGy, which is less than the extra lung dose from treatment with potentially larger ITV-based PTV approach.